SOCIOECONOMIC FACTORS ASSOCIATED WITH DIARRHEA AMONG CHILDREN UNDER FIVE YEARS IN INDONESIA: Hubungan Faktor Sosial Ekonomi Dengan Diare Pada Anak Di Bawah Usia 5 Tahun Di Indonesia - Miftahatur Rizqiyah Kurniawati; Erni Astutik (Jurnal Berkala Epidemiologi, 2023)
Introduction : The child mortality rate in the world was still relatively high, which diarrhea was one of the main causes. In Indonesia, the incidence of diarrhea in children under five years was still quite high. The aim of this study was to determine the relationship between socioeconomic factors and the diarrhea in toddlers. Methods : This study used secondary data taken from the 2017 Indonesian Health Demographic Survey dataset. The sample of this study was 13,830 mothers aged 15-49 years. The criteria inclusions were a mother who were completely interviewed, had children less than 5 years, last child and lived together, and was still alive. Data were analyzed using multiple logistic regressions. Results and Discussion : The results showed that there were 14.7% of mothers whose children were less than 5 years old experienced diarrhea recently. Husbands/partners with middle education had 17% higher odds of their children having diarrhea compared to husbands/partners with higher education (AOR=1.17 ; 95%Cl=1.02–1.33 ; p=0.024). Toddlers with very poor (AOR=1.39 ; 95%Cl=1.12–1.73 ; p=0.003), poor (AOR=1.36 ; 95%Cl=1.11–11.67; p=0.004), and rich (AOR=1.24 ; 95%CI=1,01–1.52 ; p=0.039) socioeconomic had 39%, 36%, 24% higher odds for their children to have diarrhea when compared to toddlers with very rich family backgrounds. Conclusion : The husband's/partners with lower education and lower socioeconomic status had higher risk for their children to experience diarrhea. Therefore, improving the welfare and economy of the community as well as improving the quality of education and public knowledge, especially regarding children's health, is urgently needed in efforts to prevent and reduce the diarrhea.